PENGARUH LINGKUNGAN KERJA DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HOTEL THE OBEROI BEACH RESORT BALI - Gunawan Wibisono; Dewanti Sujadi; Ni Kadek Ayu Fitriani (Universitas Triatma Mulya, 2021)
The problem raised in this study is whether the Work Environment (X1) affects the Employee Work Productivity (Y) at The Oberoi Beach Resort Bali Hotel, does Job Training (X2) affect the Employee Work Productivity (Y) at The Oberoi Beach Resort Bali Hotel, what is the influence of Work Environment and Work Training on Employee Work Productivity at The Oberoi Beach Resort Bali Hotel and how much influence these two independent variables have on Employee Work Productivity at The Oberoi Beach Resort Bali Hotel and which independent variables have a dominant influence on Employee Work Productivity at The Oberoi Beach Resort Bali Hotel. Obtained Environmentally (X1) has a positive and significant influence on Work Productivity (Y) at The Oberoi Beach Resort Bali Hotel which is indicated by a positive coefficient b1X1 regression coefficient of 0.194. Job Training (X2) has a positive and significant influence on Work Productivity (Y) at The Oberoi Beach Resort Bali Hotel, this can be seen in the positive coefficient b2X2 of 0.375. The Effect of Work Environment and Work Training on Employee Productivity at The Oberoi Beach Resort Hotel in Bali by 54% with Work Training as the dominant variable affecting Employee Productivity with a Coefficients Beta value of 0.551.